From 'Uqūbah To 'Ibrah: A Theo-Pedagogical Reinterpretation of Jinayat Verses for Character Education in the Digital Era - Junaedi (Kartika: Jurnal Studi Keislaman, 2026)
This article executes a paradigmatic shift in jinayat verse hermeneutics, reinterpreting Islamic criminal law from punitive legal texts to potent moral education sources. The dominant legal-formalist paradigm, focused on punishment ('uqūbah), proves inadequate for contemporary digital moral crises. Employing a theo-pedagogical framework grounded in Maqāṣid al-Sharī'ah philosophy and utilizing Tafsīr Tarbawī methodology, this research demonstrates that Qur'anic prohibitions contain profound pedagogical purposes ('ibrah). Using Tafsīr Tarbawī methodology, this study extracts fundamental principles from verses concerning adultery, theft, false accusation, retaliation, and rebellion, identifying relational ethics, economic integrity, information responsibility, restorative justice, and civic cohesion. These principles synthesize into a three-pillar digital character education framework addressing cybercrime, disinformation, cyberbullying, and online exploitation. The principal contribution is a comprehensive Qur'an-based educational model transforming scriptural threats into transformative lessons, providing robust moral foundations for cyberspace integrity.